Preparation method of fluorocarbon clay stabilizer for oil and gas fields
By introducing fluorocarbon chains to prepare fluorocarbon soil stabilizers, the problem of hydration and expansion of clay minerals in oil and gas field development has been solved, and the hydrophobic and anti-swelling properties of the stabilizers have been significantly improved. It is suitable for complex reservoir environments and provides more efficient and reliable oil field development solutions.
Patent Information
- Application Number
- CN202510238997.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2045-03-03
AI Technical Summary
During the development of oil and gas fields, the hydration and expansion of clay minerals lead to problems such as collapse of well walls, drilling, crack closure, and degradation of flow diversion capacity. Traditional stabilizers lack stability and limited applicability in complex reservoir environments.
The fluorocarbon clay stabilizer is prepared by introducing fluorocarbon chains. By forming a hydrophobic protective film on the surface of clay minerals, water molecules are prevented from entering, thereby inhibiting hydration and expansion. By reasonably designing monomer ratios and polymerization processes, the thermal stability and applicability of the stabilizer are improved.
It significantly improves the hydrophobic properties and anti-swelling properties of the stabilizer, overcomes the problems of insufficient stability and limited applicability of traditional stabilizers in complex reservoir environments, and provides a more efficient and reliable solution for oilfield development.
Smart Images

Figure CN119735742A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas exploitation and oilfield chemistry, and relates to a method for preparing a fluorocarbon clay stabilizer for oil and gas fields. Background Art
[0002] In the process of oil and gas field development, drilling, fracturing and water injection operations are three key links, and the hydration and expansion of clay minerals is a common technical problem in the above operations. Clay minerals (such as montmorillonite, illite, rectorite, etc.) are widely present in sedimentary rocks. When they encounter water, they will hydrate and expand, resulting in rock structure destruction, reduced formation permeability and deterioration of working fluid performance. For example, during the drilling process, after the drilling fluid comes into contact with the clay minerals in the formation, the clay minerals will hydrate and expand, which may cause well wall collapse, drill stuck and other problems, seriously affecting drilling efficiency and safety; in shale gas development, after the fracturing fluid comes into contact with the clay minerals in the formation, the hydration and expansion of the clay minerals will cause the cracks to close and the conductivity to decrease, thereby reducing the fracturing effect; in the later stage of oil field development, after the injected water comes into contact with the clay minerals in the formation, the hydration and expansion of the clay minerals will cause the formation porosity to decrease and the permeability to decrease, thereby affecting the water injection effect and the final crude oil recovery rate.
[0003] In recent years, in response to the reservoir damage caused by the hydration and expansion of clay minerals during oil and gas production, domestic and foreign scholars have successively developed a variety of clay stabilizers, mainly including inorganic salts, inorganic cationic polymers, surfactants and organic cationic polymers. Among them, inorganic salts inhibit the hydration and expansion of clay minerals through ion exchange and double layer compression effect, and have the advantages of low cost and strong adaptability. However, the radius of inorganic cations is small, and ion diffusion and ion exchange are easy to lead to desorption, reducing their long-term inhibition ability. Trivalent and above metal ions in inorganic cationic polymers can dissociate under specific conditions to form multi-nuclear hydroxyl bridged complexes, which neutralize the negative charge on the clay surface through electrostatic adsorption, thereby inhibiting expansion and particle migration. Compared with inorganic salts, its stabilization effect is more lasting, but when the pH value is non-neutral, the anti-swelling efficiency is reduced. Cationic surfactants achieve clay stabilization through charge neutralization and wettability regulation, but they have limitations in practical applications; surfactant molecule adsorption may induce wetting reversal phenomenon, forming liquid phase closure, and aggravating the water lock effect of the reservoir. Organic cationic polymers have the characteristics of low dosage, strong adsorption, and acid and alkali resistance. However, their relative molecular mass is relatively high, and they are prone to physical blockage at the pore throats of low permeability reservoirs, resulting in secondary permeability damage, which restricts their applicability in complex reservoirs.
[0004] In view of the problem that the above-mentioned clay stabilizers have limited applicability in certain complex reservoirs, the present invention prepares fluorocarbon clay stabilizers by introducing fluorocarbon chains, which not only significantly improves the hydrophobicity and anti-swelling properties of the stabilizer, but also overcomes the problems of insufficient stability and limited applicability of traditional stabilizers in complex reservoir environments, thereby providing a more efficient and reliable solution for drilling, fracturing and water injection operations in oil field development. Summary of the invention
[0005] The present invention introduces a fluorocarbon chain to prepare a fluorocarbon clay stabilizer, which significantly improves the hydrophobicity and thermal stability of the stabilizer; the fluorocarbon chain has extremely strong hydrophobicity and can form a hydrophobic protective film on the surface of clay minerals, effectively preventing water molecules from entering the interior of clay particles, thereby significantly inhibiting the hydration expansion of the clay; at the same time, the fluorocarbon chain has excellent thermal stability, is not easy to decompose and fail under high temperature and high pressure environments, and can meet the needs under complex geological conditions; in addition, by reasonably designing the monomer ratio and polymerization process, the obtained stabilizer can produce a good inhibitory and anti-swelling effect on various types of clay minerals (such as montmorillonite, illite, rectorite, etc.).
[0006] The technical solution of the present invention to solve the above technical problems is as follows: A method for preparing a fluorocarbon clay stabilizer for oil and gas fields comprises the following steps: Step 1: Add three monomers, acrylamide, acrylic acid and fluorinated acrylate, in a container in order, with the weight ratios of 300 parts, 195-150 parts and 5-50 parts respectively, and then add 675-1350 parts of solvent N,N-dimethylformamide; stir and dissolve at room temperature, introduce nitrogen to deoxygenate, and heat to 50°C for standby use; Step 2: Take 1-4 parts of azobisisobutyronitrile as an initiator, add 75-150 parts of N,N-dimethylformamide as a solvent, and dissolve to obtain an initiator solution; Step 3: Under a nitrogen atmosphere, slowly drop the initiator solution obtained in step 2 into the monomer mixed solution obtained in step 1 for 15 min to 30 min, and slowly heat to 60°C to 75°C, stir, and perform polymerization for 5 h to 10 h; Step 4: The reaction product obtained in step 3 is cooled to room temperature, precipitated with anhydrous ethanol, shredded, washed, filtered, vacuum dried at 50°C to 70°C for 24 h to 48 h, and crushed to obtain a fluorocarbon clay stabilizer.
[0007] Furthermore, in step 1, the fluorocarbon chain (—C m F n ) m 3~8, the number of fluorine atoms n From 6 to 17.
[0008] The present invention also provides an application of a fluorocarbon clay stabilizer in the fields of oil and gas field drilling, fracturing, and water injection development, wherein the mass concentration of the fluorocarbon clay stabilizer is 0.2% to 2.0%.
[0009] The beneficial effects of the present invention are: The present invention prepares a fluorocarbon clay stabilizer by introducing a fluorocarbon chain, which has excellent anti-hydration expansion performance, chemical stability and thermal stability. It not only significantly improves the hydrophobicity and anti-swelling performance of the stabilizer, but also overcomes the problems of insufficient stability and limited applicability of traditional stabilizers in complex reservoir environments, and provides a more efficient and reliable solution for drilling, fracturing and water injection operations in oil field development, which is in line with social and economic benefits and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is the reaction equation diagram of fluorocarbon clay stabilizer; Figure 2 This is the infrared spectrum of clay stabilizer PAF-13; Figure 3 The infrared spectra of monomers AM, AA, FA13 and clay stabilizer PAF-13; Figure 4 This is the contact angle test diagram of distilled water and clay stabilizer PAF-13 on rectorite; Figure 5 This is the contact angle test diagram of distilled water and clay stabilizer PAF-13 on illite; Figure 6 It is the expansion curve of distilled water and clay stabilizer PAF-13 on rectorite; Figure 7 This is the expansion curve of distilled water and clay stabilizer PAF-13 on illite. DETAILED DESCRIPTION
[0011] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0012] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0013] The present invention provides a method for preparing a fluorocarbon clay stabilizer for oil and gas fields, comprising the following steps: Step 1: Add three monomers, acrylamide, acrylic acid and fluorinated acrylate, in a container in sequence, with the weight of the monomers being 300 parts, 195-150 parts and 5-50 parts respectively, and then add 675-1350 parts of solvent N,N-dimethylformamide; stir and dissolve at room temperature, introduce nitrogen to deoxygenate, and heat to 50°C for standby use; Step 2: Take 1-4 parts of azobisisobutyronitrile as an initiator, add 75-150 parts of N,N-dimethylformamide as a solvent, and dissolve to obtain an initiator solution; Step 3: Under a nitrogen atmosphere, slowly drop the initiator solution obtained in step 2 into the monomer mixed solution obtained in step 1 for 15 min to 30 min, and slowly heat to 60°C to 75°C, stir, and perform polymerization for 5 h to 10 h; Step 4: The reaction product obtained in step 3 is cooled to room temperature, precipitated with anhydrous ethanol, shredded, washed, filtered, vacuum dried at 50°C to 70°C for 24 h to 48 h, and crushed to obtain a fluorocarbon clay stabilizer.
[0014] The specific reaction equation is shown in Figure 1 , where R is a fluorocarbon chain (—C m F n ), m 3~8, n From 6 to 17.
[0015] The present invention also provides an application of a fluorocarbon clay stabilizer in the fields of oil field drilling, fracturing and water injection development, wherein the mass concentration of the fluorocarbon clay stabilizer is 0.2% to 2.0%.
[0016] Example 1: Using acrylamide, acrylic acid, and tridecafluorooctyl acrylate as monomers, a fluorocarbon clay stabilizer PAF-13 was prepared. The specific implementation steps are as follows: Step 1: Add 6.0 g of reaction monomer acrylamide (AM), 3.40 mL of acrylic acid (AA), 0.33 mL of tridecafluorooctyl acrylate (FA13) and 30.0 mL of solvent N,N-dimethylformamide (DMF) into a three-necked flask in sequence, stir to dissolve at room temperature, introduce nitrogen to deoxygenate, and heat to 50°C for use; Step 2: Dissolve 0.04 g of initiator azobisisobutyronitrile (AIBN) in 3 mL of solvent N,N-dimethylformamide to obtain an initiator solution; Step 3: In a nitrogen atmosphere, slowly drop the initiator solution obtained in step 2 into the monomer mixed solution obtained in step 1, and slowly heat the mixture to 65°C. The dropping time and heating time are controlled within 15 min to 30 min. Stir and perform the polymerization reaction for 6 h. Step 4: The reaction product obtained in step 3 is cooled to room temperature, precipitated with anhydrous ethanol, shredded, washed, filtered, vacuum dried at 65° C. for 48 h, and crushed to obtain a fluorocarbon clay stabilizer PAF-13.
[0017] The fluorocarbon clay stabilizer prepared in the above example was characterized for its molecular structure, and its ability to inhibit swelling of common clay minerals (rectorite, illite) in oilfield development was further evaluated. The relevant test results are as follows: 1. Clay stabilizer structure characterization The clay stabilizer prepared in the example was vacuum dried and then a small amount was taken out, mixed evenly with potassium bromide (spectrally pure), pressed into tablets, and then tested using a Fourier infrared spectrometer. The experimental results are as follows: Figure 2 Acrylamide, acrylic acid, and tridecafluorooctyl acrylate were tested by the same potassium bromide tablet method using a Fourier transform infrared spectrometer. The experimental results are shown in Figure 3 shown.
[0018] Figure 2 This is the infrared spectrum of clay stabilizer PAF-13, in wavenumber / cm -1 is the horizontal axis, and the transmittance / % is the vertical axis. Figure 2 It can be obtained that 3549 cm -1 and 3471 cm -1 The peak at 3418 cm is the characteristic peak of O—H stretching vibration in the carboxyl group (—COOH); -1 With 3214 cm -1 The "double peak" at 2947 cm is the characteristic peak of the stretching vibration of N-H in primary amide (O=CH-NH2); -1 The peak at 1719 cm is the characteristic peak of the stretching vibration of -CH2- in the carbon chain; -1 The peak at 1654 cm is the characteristic peak of the stretching vibration of C=O in the ester group (—COOR); -1 The peak at 1449 cm is the stretching vibration characteristic peak of C=O in carboxyl and primary amide; -1 The peak at 1404 cm is the characteristic peak of the bending vibration of -CH2- in the carbon chain; -1 The peak at 1240 cm is the characteristic peak of C—N stretching vibration in primary amide; -1 、1113cm -1 The 1187cm-1 is the characteristic peak of the bending vibration of C-F in -CF3 and -CF2; -1 The peak at 618cm is the characteristic peak of C—O—C stretching vibration in the ester group; -1 The peak is the characteristic bending vibration peak of -NH2 in primary amide.
[0019] Figure 3The infrared spectra of monomers AM, AA, FA13 and clay stabilizer PAF-13 are shown in wavenumber / cm -1 The horizontal axis is the transmittance / % and the vertical axis is the transmittance / %. By comparing the infrared spectra of monomers AM, AA, FA13 and their synthesized clay stabilizer PAF-13, it was found that the stretching vibration characteristic peak of the primary amide N—H in AM (3364 cm -1 、3179 cm -1 ), the stretching vibration characteristic peak of the carboxyl O—H in AA (3413 cm -1 ), the stretching vibration characteristic peaks of the ester group C=O and C—O—C in FA13 (1743 cm -1 、1195 cm -1 ) and the characteristic peak of bending vibration of C-F in the fluorocarbon chain (1248 cm -1 , 1080 cm -1 ) is basically consistent with the corresponding characteristic peak position in the infrared spectrum of PAF-13. At the same time, the C=C stretching vibration characteristic peak (1629 cm -1 、1563 cm -1 、1612cm -1 ) disappeared in the infrared spectrum of PAF-13. Therefore, it can be proved that all three monomers participated in the polymerization reaction and the synthesis was successful.
[0020] 2. Evaluation of clay stabilizer performance (1) Contact angle test The rectorite or illite powder was pressed into a cylindrical specimen with a diameter of 18 mm and a thickness of 2 mm and a smooth plane. The contact angles of distilled water and clay stabilizer PAF-13 solution (mass concentration of 1.0%) on the surface of the rectorite or illite specimen were measured by the hanging drop method using an SDC-350 contact angle meter.
[0021] Figure 4 is the contact angle of distilled water and clay stabilizer PAF-13 on rectorite; Figure 4 It can be seen that the contact angle between distilled water and the surface of rectorite is 34.07°, which is highly hydrophilic. After adding the clay stabilizer PAF-13, the contact angle between the solution and the surface of rectorite increases to 55.99°, which reduces the hydrophilicity of the surface of rectorite.
[0022] Figure 5 is the contact angle of distilled water and clay stabilizer PAF-13 on illite; Figure 5 It can be seen that the contact angle between distilled water and the illite surface is 27.90°, which is highly hydrophilic. After adding the clay stabilizer PAF-13, the contact angle between the solution and the rectorite surface increases to 39.41°, which reduces the hydrophilicity of the illite surface.
[0023] (2) Anti-swelling performance test 1) Linear expansion coefficient V H According to the "Mud Shale Expansion Test" method in the "Test Methods for Physical and Chemical Properties of Mud Shale" (SY / T 5613-2000), rectorite and illite cores were prepared, and the original thickness H (mm) of the cores was measured with a vernier caliper. The NP-01 shale expansion instrument was used to fill the measuring cylinder with the test fluid, i.e., distilled water or clay stabilizer PAF-13 solution (mass concentration of 1.0%), and the expansion coefficients at different times were obtained. t Linear expansion R t (mm). Calculate the linear expansion rate V for 2 h, 8 h or 16 h according to the following formula. H (%): V H = R t / H × 100% Table 1 Linear expansion coefficients of clay minerals in different fluids Figure 6 The expansion curves of distilled water and clay stabilizer PAF-13 on rectorite. Figure 6 It can be seen that in distilled water, rectorite has a particularly significant hydration expansion, and the linear expansion rate increases sharply. After 20 minutes, the linear expansion rate is as high as 16.79%. After 2 hours, the increase in the linear expansion rate tends to be flat, V 2h 、V 8h In the clay stabilizer PAF-13 solution (mass concentration of 1.0%), the hydration expansion of rectorite was suppressed. No obvious hydration expansion occurred within 20 minutes, and the linear expansion rate growth trend was obviously flat. After 2 hours, the linear expansion rate was only 6.19%, which was 87.15% lower than that in distilled water. 8h The linear expansion rate is 21.89%, which is only 39.66% of the linear expansion rate in distilled water. After 12 h, the linear expansion rate remains basically unchanged. 16h As low as 27.21%, indicating that the clay stabilizer PAF-13 has excellent anti-hydration expansion performance for rectorite.
[0024] Figure 7 The expansion curves of distilled water and clay stabilizer PAF-13 on illite. Figure 7 It can be seen that in distilled water, illite also showed particularly significant hydration expansion, and the linear expansion rate increased sharply. After 20 minutes, the linear expansion rate was as high as 19.00%. After 30 minutes, the increase in the linear expansion rate tended to be flat, V 2h 、V 8hIn the clay stabilizer PAF-13 solution (mass concentration of 1.0%), the hydration expansion of illite was suppressed. After 30 minutes, the linear expansion rate increased significantly and was only 7.62% after 2 hours. Compared with distilled water, the linear expansion rate decreased by 65.70%. 8h The linear expansion rate is 9.76%, which is only 57.21% of that in distilled water. 16h It is only 10.82%, indicating that the clay stabilizer PAF-13 also has excellent anti-hydration expansion performance for illite.
[0025] 2) Anti-swelling rate B1 According to the "Determination of Expansion Volume" (centrifugation method) in the "Performance Evaluation Method of Clay Stabilizer for Fracturing Acidification and Water Injection in Oil and Gas Fields" (SY / T 5971-2016), weigh a certain mass of clay mineral powder (for later reading), accurate to 0.01g, put it into a 10 mL centrifuge tube, add clay stabilizer PAF-13 solution (mass concentration of 1.0%), shake it thoroughly, leave it at room temperature for 2 hours, put it into a centrifuge, centrifuge it at a speed of 1500 r / min for 15 minutes, and read the volume V1 (mL) of the clay mineral after expansion. Repeat the experiment, use distilled water and kerosene instead of clay stabilizer solution, respectively, and determine the expansion volume of clay minerals in distilled water and kerosene, that is, V2 (mL) and V3 (mL). Calculate the anti-swelling rate B1 (%) according to the following formula: B1=[(V2—V1) / (V2—V0)]×100% The test results show that the fluorocarbon clay stabilizer PAF-13 solution with a mass concentration of 1.0% has a good ability to inhibit the swelling of rectorite and illite, and the anti-swelling rates are 91.28% and 85.92% respectively.
[0026] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a fluorocarbon clay stabilizer for oil and gas fields, characterized in that: The following steps are involved: Step 1: Add three monomers, acrylamide, acrylic acid and fluorinated acrylate, in a container in order, with the weight ratios of 300 parts, 195-150 parts and 5-50 parts respectively, and then add 675-1350 parts of solvent N,N-dimethylformamide; stir and dissolve at room temperature, introduce nitrogen to deoxygenate, and heat to 50°C for standby use; Step 2: Take 1-4 parts of azobisisobutyronitrile as an initiator, add 75-150 parts of N,N-dimethylformamide as a solvent, and dissolve to obtain an initiator solution; Step 3: Under a nitrogen atmosphere, slowly drop the initiator solution obtained in step 2 into the monomer mixed solution obtained in step 1 for 15 min to 30 min, and slowly heat to 60°C to 75°C, stir, and perform polymerization for 5 h to 10 h; Step 4: The reaction product obtained in step 3 is cooled to room temperature, precipitated with anhydrous ethanol, shredded, washed, filtered, vacuum dried at 50°C to 70°C for 24 h to 48 h, and crushed to obtain a fluorocarbon clay stabilizer.
2. The method for preparing a fluorocarbon clay stabilizer for oil and gas fields according to claim 1, characterized in that: The fluorine-containing acrylic ester monomer has a fluorine-carbon chain (—C m F n ) m 3~8, the number of fluorine atoms n From 6 to 17.
Citation Information
Patent Citations
Fluorine-silicon-containing polymer shale inhibitor for water-based drilling fluid and preparation method of fluorine-silicon-containing polymer shale inhibitor
CN114573771A
Drag reducer for fracturing and preparation method thereof
CN118580438A
Rubber mixture, nitrile group-containing copolymer rubber composition, crosslinkable rubber composition, and crosslinked rubber
JP2020050722A
Shrinkage-reducing ultra high early strength and early strength cement concrete composition and repairing method for road pavement using the same
KR102414943B1
Chain-End Functionalized Fluoropolymers for the Preparation of Fluorpolymer / Clay Nanocomposites with Exfoliated Structure
US20080058454A1
Cited By
A fracturing fluid system for coalbed methane development and its preparation method
CN122668732A